The Effect of Rhyme on the External Rhythmic Structure and Textual Semantics in the Diwan of Ibn Shuhayd al-Andalusi - Ibrahim Al-Shboul, Walaa; M. Al-Absi, Mohammad (Arts and Social Sciences Series, 2026)
This study aims to examine the effect of rhyme on the external rhythmic structure and textual semantics in the Diwan of Ibn Shuhayd al-Andalusi, considering rhyme a central structural element in shaping the external rhythmic structure of classical Arabic poetry and the semantic effects that extend beyond the individual verse to encompass the text as a whole. The study is grounded in the problematic relationship between phonetic structure and semantic structure, within a structuralist framework that views meaning as the result of the interaction of various linguistic levels within the text. It seeks to reveal the role of rhyme in constructing external rhythm on the one hand, and in directing textual meaning on the other, through an applied analysis of Ibn Shuhayd al-Andalusi’s poetry, which is characterized by notable variations in rhyme that allow for a clear examination of the phenomenon. The study adopts a descriptive–analytical approach, supported by a statistical method when necessary, particularly in tracing open and restricted rhymes, following a brief theoretical introduction that defines the concept of rhyme and its terminological boundaries. The research is divided into three sections: the first examines rhyme as a means of achieving rhythmic unity in the poem; the second addresses the phenomenon of open and restricted rhymes and their effect on phonetic structure; while the third adopts an integrative approach to explore the interaction between rhyme, external rhythm, and textual semantics. The findings indicate that rhyme in the poetry of Ibn Shuhayd al-Andalusi does not merely serve a formal musical function; rather, it plays an active role in constructing and stabilizing external rhythm, while simultaneously contributing to the direction of meaning and the establishment of semantic coherence among the verses and sections of the poem. The results further demonstrate that the selection and phonetic construction of rhyme are closely related to the semantic context of the text, confirming the presence of an interactive relationship between sound and meaning in shaping Andalusian poetic discourse.